The Successful Usage of the DICOM Images Exchange System (ePACS) in the Czech Republic - Bruthans, Jan (Applied Clinical Informatics, 2020)
Background The picture archiving and communication system (PACS) has already replaced classic hard copy film technology. With new functions of PACS under consideration, attention turns to the sharing of medical images between different institutions. The Czech Republic is one of the few countries using a nation-wide medical images exchange system known as ePACS. It is based on dedicated hardware and one central router, although theoretical models tend to prefer cloud-based sharing.Objective Despite its simple design and lack of advanced features, this system has successively evolved into a widely used tool. The aim of this article is to offer an overview of its use and functions and to show that even a simple system can be widely used.Methods Using data from the producer of ePACS (the ICZ company) and from other sources, the system was described and data about its performance have been obtained.Results Every acute-care hospital (140) and about a quarter of outpatient facilities (105) in the Czech Republic are now equipped with ePACS and are therefore able to share medical images. The number of studies transmitted rises every year, from 12,000 in 2008 to more than 640,000 in 2018, which is approximately 4% of all studies produced. The system was primarily designed and is used to share images between acute-care hospitals but a very special usage has also evolved, as it is employed in a teleradiology service with private enterprises too.Conclusion ePACS is expanding in the Czech Republic despite having only limited functions and despite its principle that simply copies a classic workflow when sending studies on Compact Discs. Although other systems for image sharing might be more advanced, ePACS brings to the Czech health care system the capability to exchange medical images on a national level.
Keywords: DICOM; PACS; information systems; cloud computing; radiology information systems